The Palace of Minos 4 Volume Set : A Comparative Account of the Successive Stages of the Early Cretan Civilization as Illustrated by the Discoveries at Knossos : Volume 1: The Neolithic and Early and Middle Minoan Ages - Evans, Arthur Sir (Cambridge library collection. Archaeology, 1921)
Inspired by Schliemann's discoveries at Mycenae and Troy, Sir Arthur John Evans (1851–1941), keeper of Oxford's Ashmolean Museum from 1884 to 1908, trustee of the British Museum and fellow of the Royal Society, used his inherited wealth to purchase land in Crete at Knossos. From 1900 he commenced excavations there in co-operation with the British School at Athens. Work continued for eight full seasons, uncovering a Bronze Age palace and bringing to light further architectural and artefactual remains of Minoan civilisation, including numerous texts in Linear A and Linear B. Evans' speculative reconstruction of the site in reinforced concrete remains controversial, and some of his interpretations are disputed, but his pioneering work is painstakingly detailed in this highly illustrated multi-volume work, published between 1921 and 1935, with an index volume appearing in 1936. Volume 1 (1921) opens with a sketch of Minoan civilisation and then surveys its early history.